Deteksi Koi Herpesvirus (KHV) pada Ikan Nila (Oreochromis niloticus) yang Diinfeksi secara Buatan [ Detection of Koi Herpesvirus (KHV) in Nile Tilapia (Oreochromis niloticus) Infected by Artificially Infection ] - Hari Suprapto; Suwarno Suwarno; Muhammad Sungging Pradana (Jurnal Ilmiah Perikanan dan Kelautan, 2015)
Abstract Koi Herpesvirus (KHV) was formerly known as Cyprinid herpesvirus-3 (CyHV-3) and carp nephritis interstitial and necrosis gill virus (CNGV) is a virus that infects common carp and koi (Cyprinus carpio and C. carpio koi) in farmed and wild population. KHV cause disease at a temperature of 18-25 °C with mortality rate of 80-90 % in fry and adult fish. Currently KHV also detected in tilapia from the results of monitoring in the field. The presence of KHV in tilapia can occur as a result of maintenance in cages adjacent to the infected carp. KHV diagnostic method currently based on case definition and PCR (Polymerase Chain Reaction) detection. The basic concept of PCR is one DNA molecule is used to produce two copies, then four, then eight and so forth through multiplication by polymerase. PCR results sometimes indicated the presence of a faint band caused a low amount of virus, so it is necessary to investigate the presence of KHV DNA in tilapia using different doses of infection. This study aimed to determine the KHV infectivity in nile tilapia were infected by artificially infection and determine dose KHV infection that can infect nile tilapia. The study design used true experimental with with the presentation of descriptive data. Dose of viral infection are 1 ID50, 10 ID50, 100 ID50 and 1000 ID50. The results showed that no clinical symptoms of KHV infected in nile tilapia. The results of electrophoresis of PCR products showed that the mucus of nile tilapia were infected with a 1000 ID50 immersion dose showed thin bands. The same results are also shown in the gill of nile tilapia infected by gill spray at 1000 ID50 dose. Fish were infected by injection, KHV was not detected in mucus, gill, kidney and liver. The results above show nile tilapia cannot be infected by KHV on various treatment